2015
DOI: 10.1093/comnet/cnv022
|View full text |Cite
|
Sign up to set email alerts
|

Detecting global bridges in networks

Abstract: The identification of nodes occupying important positions in a network structure is crucial for the understanding of the associated real-world system. Usually, betweenness centrality (BC) is used to evaluate a node capacity to connect different graph regions. However, we argue here that this measure is not adapted for that task, as it gives equal weight to 'local' centres (i.e. nodes of high-degree central to a single region) and to 'global' bridges, which connect different communities. This distinction is imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 26 publications
0
47
0
Order By: Relevance
“…However, they provide an incomplete picture. Indeed, they miss weak ties that have been identified as crucial connections to bridge separated clusters of individuals, thus fundamental for large scale outbreaks [348,673,674].…”
Section: Measuring and Understanding Close Proximity Interactionsmentioning
confidence: 99%
“…However, they provide an incomplete picture. Indeed, they miss weak ties that have been identified as crucial connections to bridge separated clusters of individuals, thus fundamental for large scale outbreaks [348,673,674].…”
Section: Measuring and Understanding Close Proximity Interactionsmentioning
confidence: 99%
“…This strategy performs better than the Betweenness-based strategy in terms of the Largest Connected Component (LCC ). Bridgeness strategy is proposed by Jensen et al [90]. It is based on the Betweenness centrality while considering only shortest paths between nodes belonging to different communities.…”
Section: Non-overlapping Communitiesmentioning
confidence: 99%
“…For this, we computed these curvatures across all edges and nodes of the network and observed that the curvature for all networks (M-M7) is negative ( Figure 6, Table S1). High curvature nodes are said to be the backbone of the network those act as bridges between major network communities [89] (Figure 7, Figure S1). Since, the nodes/edges with higher curvature values act as backbone of the network [89], we wanted to look for the overall effect of these high Connected components of a network tell us about the connectivity of the nodes in the network.…”
Section: Curvature and Topological Robustness Of Modelsmentioning
confidence: 99%